Screening of early diabetic kidney disease in ShiChaHai community in Beijing - FAN Meng; DUAN Ying-wei (Linchuang shenzangbing zazhi)
Objective To study the epidemiology and management of early diabetic kidney disease in the community.Methods 120 patients diagnosed as having type 2 diabetes from January 2015 to December 2015 in ShiChaHai community in Beijing for treatment were selected as the research subjects,including 59 males and 61 females with median age of(65.31±15.27)years old.The general information,physical examination results(blood pressure,blood lipids,blood glucose,urinary albumin/creatinine),and drug and non-drug treatment in all patients were analyzed,and the risk factors associated with diabetic kidney disease were explored.Eighty physical examination volunteers with non-diabetic kidney disease in the same period were selected as the control group,including 48 males and 32 females with mean age of(64.66±13.08)years old.Results The incidence of early DKD in diabetes mellitus patients was 34.1%.The treatment nonconformance rate of blood glucose,blood pressure and lipid in early DKD group was 68.2%,78% and 65.8% respectively,and that in nonDKD group was 2.5%,25% and 26.3% respectively,with the difference being significant between two groups(P<0.05).Chi-square test suggested that age and disease duration were the risk factors of early DKD(P<0.05).In 32 cases of early DKD with blood pressure substandard,the use of angiotensin converting enzyme inhibitors(ACEI)/angiotensin II receptor ATI antagonist(ARB)was decreased.Less than half of patients were not given sufficient anti-hypertensive drugs.Sugar and lipidlowering drugs were given insufficiently in most patients.In41 early DKD patients,44% had no regular exercise,the intake of protein was not controlled in 83%,and sodium intake was not limited in70.8%.Conclusions The incidence of early DKD is still high in patients with diabetes in the community,and the standard rate of blood pressure,blood glucose,and blood lipid is still so low.The management of drug and non-drug treatment is not standardized.Early DKD is related to the age and course of diabetes.It is very necessary to carry out early screening and standard treatment of DKD in community.